Long term outcome of brain manganese deposition in patients on home parenteral nutrition. Issue 3 (1st September 1998) - Kafritsa, Yota; Fell, John; Long, Sarah; Bynevelt, Michael; Taylor, Wendy; Milla, Peter
Abstract : Manganese intoxication has been described in children on long term parenteral nutrition presenting with liver and nervous system disorders. Cases are reported of a brother and sister on long term parenteral nutrition with hypermanganesaemia and basal ganglia manganese deposition, detected by magnetic resonance imaging (MRI), without overt neurological signs. Following reduction of manganese intake, basal ganglia manganese was monitored by repeated MRI, and neurological and developmental examinations. An MRI intensity index of the globus pallidus declined over a three year period from 0.318 and 0.385 to 0.205 and 0.134 with concomitant falls in whole blood manganese from 323 and 516 to 226 and 209 nmol/l (normal range, 73–210 nmol/l). Unlike adult experience these children developed normally without neurological signs. In conclusion, deposited manganese is removed from neural tissue over time and the prognosis is good when neurological manifestations and liver disease are absent.